Enhancing renewable energy literacy through aromatic biobriquettes production training at Al-Amalul Khair Islamic Boarding School - Lety Trisnaliani; Ahmad Zikri; Ida febriana; Isnandar Yunanto; Ahmad Zydan Alhabsyi; Zahra Ananda Lanos; Nadia Melisa Fitri; Faridatuljana Binti Mohd Noor (Penamas: Journal of Community Service, 2026)
Limited renewable energy literacy and inadequate utilization of organic waste remain significant challenges in school-based environmental education. This community service program aimed to enhance renewable energy literacy and practical biomass utilization skills among students and teachers at Al-Amalul Khair Islamic Boarding School, Palembang, Indonesia, through aromatic biobriquette production training. The program employed a community-based learning approach consisting of lectures, technical demonstrations, hands-on practice, and interactive discussions. Thirty participants were involved in the activity. Program effectiveness was evaluated using a one-group pretest–posttest design. The results showed a significant increase in participants’ knowledge, with the mean score improving from 45.67 before the training to 95.00 after the training. In addition, participants demonstrated strong engagement during practical activities and expressed willingness to apply aromatic biobriquette technology for sustainable organic waste management. The findings indicate that hands-on training effectively improves renewable energy literacy and technical competencies related to biomass-based energy production.